Antibiotic prescription in Morocco, national data: Meta-analysis (Journal of Pharmaceutical Negative Results, 2022)
Antibiotics are the most prescribed medication and the misprescribing of antibiotics is a public health problem worldwide.Objective: Conduct a meta-analysis to determine the prevalence of antibiotic prescribing, assess the quality of prescribing and identify factors of inappropriate prescribing in Morocco.Materials and Methods: 92 articles found in databases (35, 42, 55 and 50, in Elsevier, PubMed, Google Scholar and Other engines respectively).Results: In studies carried out in 2009 and 2011, on the evaluation of the use of antibiotics by dermatologists we noticed that beta-lactams were the most commonly prescribed: 53%. A survey on the use of generic antibiotics or pediatric service used beta-lactam, 63%. The prescription of antibiotics in the department of burns and plastic surgery was 65%. These results are important to explain a resistance of betalactamins to different offences and the constitution of beta-lactamase should be searched. A study conducted in 2018 in Rabat, 90 physicians and surgeon’s specialists, 91.7% of them prescribed antibiotics. Through previous studies from 2014 to 2022, a children’s under 5 years of age with severe clinical pneumonia, 86.5% received antibiotics. In another study on the evaluation of antibiotic prescriptions in the emergency department, amoxicillin was used in 31.4%. Also in a study on the evaluation of antibiotic prescriptions in pediatric emergency departments, 3rd generation cephalosporins were used in 69% of cases. A study of antibiotic self-medication parents knew that antibiotics are subject to a prescription and 72.1% knew that antibiotics had side effects on children, and in this study amoxicillin was used the most at 46.6%, and it is one of the most widely used antibiotics in Morocco, despite the development of numerous resistances. In studies conducted in 2009, 2016, and 2017 on preventive antibiotic use is still prescribed (22%, 17.7% and 7.14%). Antibiotic prescriptions were not limited only to physicians, but studies indicated that 10.9% of them were prescribed by pharmacists and in 2022 the percentage increased to 42%.Conclusion: This meta-analysis on studies and research of antibiotic prescribing: national data in the last 13 years in Morocco, the deficiencies found in antibiotic prescribing require the establishment of national recommendations to reduce misprescribing.